The impact of ‘trip experience’ on the awareness of world heritage site status among tourists visiting Delhi - Juneja, Monisha; Sufi, Tahir; Bhatnagar, Mamta (Turyzm/Tourism, 2022)
Awareness of World Heritage Sites (WHS) is a marketing tool used to promote a destination. Once a tourist arrives, the ‘trip experience’ becomes a vital tool to ensure repeat visits and showcase a positive image of a destination to potential tourists. This study has tried to link the impact of the ‘trip experience’ of tourists to awareness of WHS aiming to understand the relationship of the six ‘domains’ and forming a proposed model. The data was collected from an on-site survey of 309 tourists from July to December 2019 using a structured questionnaire following a pilot study. For data analysis, logistic regression analysis was used. This revealed that four out of six domains increase the probability of tourists’ awareness of WHS status during a trip, namely: welcoming, local travel, tour leader and tour guide. The earlier model for using WHS awareness only for promotional purposes has been shifted by adding the trip experience of the tourists. The findings can be applied by tourism and hospitality facilitators in providing services to tourists.